A Method of Grading Subway Stations. (2016) - Wei, Yun; Lin, Shan; Chu, Rui; Tian, Qing; Fei, Weiwei
Abstract: This paper summarizes the classification method of domestic subway station, and points out the existing defects. In order to design of a relatively reasonable grading system, this paper reference to the existing classification method and passenger flow data. First, obtain a dynamic correction of parameters according to the static factors. Then, combine with the data of dynamic flow to determine the level of the station.